The relationships of protein, lysine and trypsin inhibitors of several strains of maize (Zea mays L.) and the properties of the inhibitors - Halim, Abdul H.; Wassom, Clyde E.; Mitchell, Howard I. (1977)
Studies were undertaken to evaluate the levels of protein, lysine and trypsin inhibitor in endosperms of genetically different strains of maize (Zea mays L.) including the isolation, purification and determination of the inhibitor properties. Endosperms containing opaque-2 gene showed a decrease in protein and increase in lysine and trypsin inhibitor contents. Floury-2 gene increased protein and lysine contents, but decreased trypsin inhibitor. However, there was no significant correlation between protein and lysine or protein and trypsin inhibitor. A significant; positive correlation was found for lysine and trypsin inhibitor, suggesting that selection for higher lysine in the endosperms of maize, especially in the opaque-2 and normal maize, would result in the inclusion of higher trypsin inhibitor. It is suggested that trypsin inhibitor assays on crude extracts of the maize endosperms could be used to evaluated lysine levels in the endosperms. There were 350 mg of purified trypsin inhibitor for one kilogram of maize kernels for the opaque-2 source and 187 mg for the normal maize. Trypsin inhibitors of maize were slowly heat labile. Kinetic studies indicated that the normal and opaque-2 sources (H28 x K41 and HL6 respectively) were competitive inhibitors, while the floury-2 source was a mixed type, having both competitive and non-competitive I inhibitors. Therefore, several types of trypsin inhibitors could be found within the maize species.